Security and Privacy in Communication Networks 18th EAI International Conference, SecureComm 2022, Virtual Event, October 2022, Proceedings - Li, Fengjun; Liang, Kaitai; Lin, Zhiqiang; Katsikas, Sokratis K. (Cham : Springer Nature Switzerland : Imprint: Springer, 2023)
This book constitutes the refereed proceedings of the 18th EAI International Conference, SecureComm 2022, Virtual Event, October 2022, Proceedings. The 43 full papers included in this book were carefully reviewed and selected from 130 submissions. They were organized in topical sections as follows: AI for Security, Applied Cryptography, Binary Analysis, Blockchain, Cryptography, Data Security, Intrusion Detection, Mobile Security, Network Security, Privacy, Software Security, Security and Privacy-preserving Solutions in the Internet of Things (S/P-IoT).
AI for Security -- Classification-Based Anomaly Prediction in XACML Policies -- An Evolutionary Learning Approach towards the Open Challenge of IoT Device Identification -- SecureBERT: A Domain-Specific Language Model for Cybersecurity -- CapsITD: Malicious Insider Threat Detection Based on Capsule Neural Network -- Towards high transferability on neural network for black-box adversarial attacks -- Coreference Resolution for Cybersecurity Entity: Towards Explicit, Comprehensive Cybersecurity Knowledge Graph with Low Redundancy -- Applied Cryptography -- Another Lattice Attack against ECDSA with the wNAF to Recover More Bits per Signature -- MAG-PUF: Magnetic Physical Unclonable Functions for Device Authentication in the IoT -- A Cross-layer Plausibly Deniable Encryption System for Mobile Devices -- Binary Analysis -- Language and platform independent attribution of heterogeneous code -- Multi-relational Instruction Association Graph for Cross-architecture Binary Similarity Comparison -- Cost-effective malware classification based on deep active learning -- Blockchain -- CTDRB: Controllable Timed Data Release using Blockchains -- FairBlock: Preventing Blockchain Front-running with Minimal Overheads -- Blockchain-based Ciphertext Policy-hiding Access Control Scheme -- Granting Access Privileges using OpenID Connect in Permissioned Distributed Ledgers -- Decentralized and Efficient Blockchain Rewriting with Bi-level Validity Verification -- Cryptography -- TERSE: Tiny Encryptions and Really Speedy Execution for Post-Quantum Private Stream Aggregation -- Symmetrical Disguise: Realizing Homomorphic Encryption Services from Symmetric Primitives -- Replicated additive secret sharing with the optimized number of shares -- Generic 2-Party PFE with Constant Rounds and Linear Active Security, and Efficient Instantiation -- Data Security -- A Random Reversible Watermarking Schefme for Relational Data -- Enabling Accurate Data Recovery for Mobile Devices against Malware Attacks -- Bootstrapping Trust in Community Repository Projects -- Intrusion Detection -- Assessing the Quality of Differentially Private Synthetic Data for Intrusion Detection -- Forensic Analysis and Detection of Spoofing based Email Attack using Memory Forensics and Machine Learning -- AttackMiner: A Graph Neural Network Based Approach for Attack Detection from Audit Logs -- Hiatus: Unsupervised Generative Approach for Detection of DoS and DDoS Attacks -- Mobile Security -- What Data Do The Google Dialer and Messages Apps On Android Send to Google? -- Detection and Privacy Leakage Analysis of Third-party Libraries in Android Apps -- Secure CV2X using COTS Smartphones over LTE Infrastructure -- Network Security -- DQR: A Double Q Learning Multi Agent Routing Protocol for Wireless Medical Sensor Network -- Message Recovery Attack of Kyber Based on Information Leakage in Decoding Operation -- PII-PSM: A New Targeted Password Strength Meter Using Personally Identifiable Information -- Privacy -- Silver Surfers on the Tech Wave: Privacy Analysis of Android Apps for the Elderly -- MetaPriv: Acting in Favor of Privacy on Social Media Platforms -- Adversary for Social Good: Leveraging AttributeObfuscating Attack to Protect User Privacy on Social Networks -- Software Security -- No-Fuzz: Efficient Anti-Fuzzing Techniques -- eSROP attack: leveraging signal handler to implement Turing-complete attack under CFI defense -- Breaking Embedded Software Homogeneity with Protocol Mutations -- Security and Privacy-preserving Solutions in the Internet of Things (S/P-IoT) -- A Generalized Unknown Malware Classification -- Research on the Grouping Method of Side-Channel Leakage Detection -- PREFHE, PREFHE-AES and PREFHE-SGX: Secure Multiparty Computation Protocols from Fully Homomorphic Encryption and Proxy ReEncryption With AES and Intel SGX.
Keywords: Data protection; Computer networks -- Security measures; Application software; Data and Information Security; Security Services; Mobile and Network Security; Computer and Information Systems Applications